Analis Sarana Dan Prasarana Pendidikan Di Lingkungan SDN 262 Panyileukan Kota Bandung - Ruslandi Ruslandi; Chaerul Rochman (IAIN Padangsidimpuan, 2019)
In the management of the school, the Headmaster must have responsible to take care of all the facilities and infrastructure. The headmaster and all of the members of the school must be able to maintain and pay attention to the facilities and infrastructure already there is. With the availability of facilities and infrastructure in schools, the students can learn maximally. The management of the schools must emphasize more attention to the facilities and infrastructure. Every people must be responsible manage and take care of these facilities and infrastructure. The head of the schools must have plans, notes, and record to any facilities and infrastructure used in the school. If all management steps have been carried out with good as expected it will have a positive impact towards students in the teaching and learning process, then the achievement of educational goals reach effectively and efficiently